2007
DOI: 10.3346/jkms.2007.22.4.762
|View full text |Cite
|
Sign up to set email alerts
|

Syringocystadenocarcinoma Papilliferum: A Case Report

Abstract: Syringocystadenocarcinoma papilliferum (SCACP) is a rare form of adenocarcinoma of the skin. This is the malignant counterpart of syringocystadenoma papilliferum (SCAP) and usually develops on the scalp in a long-standing lesion identified clinically as SCAP. We describe a 65-yr-old Korean man with a nodule on the right supra-pubic area with a 2-yr duration. Histologically this tumor had a similar overall configuration as in SCAP, but the tumor was asymmetric and poorly circumscribed, extending into the deep d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 7 publications
(19 reference statements)
1
42
0
Order By: Relevance
“…Cribriform, papillary intraductal, clinging and columnar cell patterns with focal apocrine like decapitation secretions observed, closely resembled the similarly named mammary counterparts figure 2 4 5…”
Section: Descriptionsupporting
confidence: 59%
“…Cribriform, papillary intraductal, clinging and columnar cell patterns with focal apocrine like decapitation secretions observed, closely resembled the similarly named mammary counterparts figure 2 4 5…”
Section: Descriptionsupporting
confidence: 59%
“…SCACP is a malignant form of syringocystadenoma papilliferum (SCAP). 1 Occasionally, SCAP cases present as nodular or plaque-like lesions, but SCACP is rarely seen. 2 It may develop from SCAP lesions or nevus sebaceous of Jadassohn.…”
mentioning
confidence: 99%
“…2 It may develop from SCAP lesions or nevus sebaceous of Jadassohn. 1 There have been 13 cases of SCACP reported in the literature. Here, we report and discuss the 14th case of SCACP occurring on the scalp of a 67-year-old man.…”
mentioning
confidence: 99%
“…SCACP is considered to represent the malignant counterpart of SCAP, with <10 cases having been reported so far. Most of the lesions, in fact, seem to have arisen from long‐standing SCAP (3). In 2003, Arai et al (1) reported a case of SCACP in situ , separating their lesion from conventional SCAP by the presence of a disorderly arrangement of multilayered cells with atypical nuclei.…”
mentioning
confidence: 99%